Development of classification criteria for hand osteoarthritis: comparative analyses of persons with and without hand osteoarthritis. Issue 2 (25th June 2020) - Haugen, Ida K; Felson, David T; Abhishek, Abhishek; Berenbaum, Francis; Bierma-Zeinstra, Sita; Borgen, Tove; Herrero Beaumont, Gabriel; Ishimori, Mariko; Jonsson, Helgi; Kroon, Féline PB; Maheu, Emmanuel; Ramonda, Roberta; et al.
Abstract : Objectives: Further knowledge about typical hand osteoarthritis (OA) characteristics is needed for the development of new classification criteria for hand OA. Methods: In a cross-sectional multi-centre international study, a convenience sample of patients from primary and secondary/tertiary care with a physician-based hand OA diagnosis (n = 128) were compared with controls with hand complaints due to inflammatory or non-inflammatory conditions (n = 70). We examined whether self-reported, clinical, radiographic and laboratory findings were associated with hand OA using logistic regression analyses. Discrimination between groups was assessed by calculating the area under receiver operating curves (AUC). Results: Strong associations with hand OA were observed for radiographic osteophytes (OR = 1.62, 95% CI 1.40 to 1.88) and joint space narrowing (JSN) (OR = 1.57, 95% CI 1.36 to 1.82) in the distal interphalangeal (DIP) joints with excellent discrimination (AUC = 0.82 for both). For osteophytes and JSN, we found acceptable discrimination between groups in the proximal interphalangeal joints (AUC = 0.77 and 0.78, respectively), but poorer discrimination in the first carpometacarpal joints (AUC = 0.67 and 0.63, respectively). Painful DIP joints were associated with hand OA, but were less able to discriminate between groups (AUC = 0.67). Age and family history of OA were positively associated with hand OA, whereas negative associations were found for pain, stiffness and soft tissue swelling in metacarpophalangeal joints, pain and marginal erosions in wrists, longer morning stiffness, inflammatory biomarkers and autoantibodies. Conclusions: Differences in symptoms, clinical findings, radiographic changes and laboratory tests were found in patients with hand OA versus controls. Radiographic OA features, especially in DIP joints, were best suited to discriminate between groups.